Appealing Work: An Investigation of How Ethnographic Texts Convince - Golden-Biddle, Karen; Locke, Karen (Organization Science, 1993)
This paper examines how written research accounts based on ethnography appeal to readers to find them convincing. In particular, it highlights the role of rhetoric in the readers' interaction with and interpretation of the accounts. Extending relevant work in the literatures of organization studies, anthropology and literary criticism, the paper develops three dimensions—authenticity, plausibility and criticality—central to the process of convincing. Further, through the analysis of a sample of ethnographic articles, it discloses the particular writing practices and more general strategies that make claims on readers to engage the texts and to accept that these three dimensions have been achieved. Through authenticity, ethnographic texts appeal to readers to accept that the researcher was indeed present in the field and grasped how the members understood their world. Strategies to achieve authenticity include: particularizing everyday life, delineating the relationship between the researcher and organization members, depicting the disciplined pursuit and analysis of data, and qualifying personal biases. Through plausibility, ethnographic texts make claims on readers to accept that the findings make a distinctive contribution to issues of common concern. Plausibility is accomplished by strategies that normalize unorthodox methodologies, recruit the reader, legitimate atypical situations, smooth contestable assertions, build dramatic anticipation, and differentiate the findings. Finally, through criticality, ethnographic texts endeavor to probe readers to re-examine the taken-for-granted assumptions that underly their work. Strategies to achieve criticality include: carving out room to reflect, provoking the recognition and examination of differences, and enabling readers to imagine new possibilities. The empirical analyses, which highlight both the rhetorical and substantive aspects of convincing, suggest that at a minimum ethnographic texts must achieve both authenticity and plausibility—that is, they must convey the vitality and uniqueness of the field situation and also build their case for the particular contribution of the findings to a disciplinary area of common interest. These analyses also suggest that the most provocative task and promising potential of ethnography is the use of richly-grounded data to not only reflect on the members' world, but more importantly to provoke an examination of the readers' prevailing assumptions and beliefs.